Early and Later Adoptions Have Different Long-Term Effects on Male Rat Offspring - Barbazanges, Arnaud (J Neurosci, 1996)
Both prenatal and postnatal environmental factors exert complex influences on the development of an organism. Previous studies have demonstrated that intervening events during the prenatal period can have different and even opposite effects than similar intervening events occurring in the postnatal period. We have reported previously that early postnatal adoption prevents prenatal stress-induced long-term impairments in glucocorticoid feedback. To characterize further the effects of adoptions during the postnatal period, adoptions have been performed at different times, and the effect on the postnatal ontogeny of the hypothalamo–pituitary–adrenal axis has been investigated. Adoptions were performed during the first hour after birth (A1) and on the fifth (A5) and twelfth (A12) days after birth. At each of these times, other litters (S1, S5, S12) underwent a “separation” controlling for the 1 min maternal separation necessary for the adoptions. Locomotor behavior, cognition, and stress-induced corticosterone secretion in the adult male offspring have been examined, along with maternal behavior. Early adoption (A1) was found to prevent the prolonged stress-induced secretion of corticosterone evident in early separated (S1) offspring. Similarly, A1 rats demonstrated lower novelty-induced locomotion and improved recognition performance in a Y-maze compared to S1 offspring. However, later adoption (A5, A12) prolonged stress-induced corticosterone secretion, increased the locomotor response to novelty, and disrupted cognitive performance in the offspring. Only the early adoption increased maternal licking behavior, a factor that may have a protective effect on the pups. Taken together, these results suggest that the same postnatal manipulation realized at different times can induce different, or even opposite, effects on the behavioral and neuroendocrine characteristics of the adult offspring.